DAMPAK KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN ANAHATA VILLAS AND SPA RESORT UBUD - I Wayan Meryawan (UHN IGB Sugriwa Denpasar, 2024)
The level of satisfaction of hotel visitors with the facilities and service quality is formed based on the experience they have gained. Weak service quality and facility quality cause weak hotel guest satisfaction levels. This study explores how far the impact of service quality and facilities can affect guest satisfaction of Anahata Villas And Spa Resort Ubud. The research uses a quantitative approach by involving a data collection method through a questionnaire which is distributed as many as 96 visitors to domestic tourist guests. Descriptive analysis was used to test the research hypothesis by using the analysis of the validity test of the reliability of the instrument, the t-test and the f-test. The results of the study provide results that the quality of service and facilities independently is proven to play a role in increasing consumer satisfaction as evidenced by the results of obtaining t-test scores that exceed the t-table values and when viewed simultaneously that the quality of service and facilities has a positive and significant effect in building visitor satisfaction of Anahata Villas And Spa Resort Ubud. This result can provide reinforcement for the tourism industry to be able to strengthen the assessment of hotel guest satisfaction through the important role of directly perceived service quality and facilities as indirect service support.